LEVERAGING FINANCIAL TECHONOLOGY AND FINANCIAL LITERACY INTO BUSINESS SUSTAINABILITY AND ITS IMPACT ON PERFORMANCE OF MSMEs - Nur Fitri Dewi (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
The development of MSMEs in Indonesia is currently very dynamic. However, there are still many MSME players who may not fully understand the importance of financial technology and financial literacy in their business, including in Alang - Alang Lebar District, Palembang, South Sumatra. The aim of this research is to determine the influence of financial technology and financial literacy on business sustainability and its impact on the performance of MSMEs in Alang - Alang Lebar, Palembang. The population of this research is Alang – Alang Lebar MSMEs. The data collection method was a questionnaire distributed to 100 samples. The data was processed using SPSS 27.00 with t test and Path Analysis. The research results show that financial technology and financial literacy do not have a positive impact on business sustainability. Financial technology and financial literacy have a positive significant impact on the performance of MSMEs in Alang - Alang Lebar, both directly and indirectly mediated by business sustainability. Moreover, business sustainability has a direct effect on performance of MSMEs. The results of this research can be benefical for MSMEs as input and consideration in determining strategies, especially regarding business sustainability and perfomance of MSMEs in Alang - Alang Lebar.